Die absolute Schweine CD : 32 saustarke Songs - Various (Falcon Neue Medien, 2001)
Steppenwolf: Born To Be Wild / Shocking Blue: Venus / Roger Miller: King Of The Road / Village People: YMCA / Santa Esmeralda & Leroy Gomez: Don't Let Me Be Misunderstood / The Turtles: Happy Together / Mungo Jerry: In The Summertime / Chris Montez: Let's Dance / The Kinks: Lola / The Equals: Baby Come Back / The Archies: Sugar Sugar / Trini Lopez: La Bamba / Ohio Express: Yummy Yummy Yummy / The Rubettes: Sugar Baby Love / Marc Bolan & T. Rex: Metal Guru / The Les Humphries Singers: Mexico CD 2: Gloria Gaynor: I Will Survive / Hot Chocolate: You Sexy Thing / Chris Andrews: Yesterday Man / The Sweet: Ballroom Blitz / Mud: Dynamite / Manfred Mann: Pretty Flamingo / The Smoke: My Friend Jack / F.R. David: Words / Steam: Na Na Hey Kiss Him Good Bye / 1910 Fruitgum Company: Simon Says / The Tornados: Telstar / The Tremeloes: Here Comes My Baby / Leapy Lee:. Little Arrows / Middle OfChirpy Chirpy Cheap Cheap / The Swinging Blue Jeans: Hippy Hippy Shake / Roy Orbison: Oh, Pretty Woman